2005
DOI: 10.1080/02699050400025042
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of treatments for mild traumatic brain injury

Abstract: There are few rigorous studies evaluating treatment of MTBI. Limitations of the current literature are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(156 citation statements)
references
References 44 publications
4
149
0
1
Order By: Relevance
“…Included in the online supplemental materials, Appendix A includes the references for all 131 studies. cognitive outcomes (Comper, Hutchison, Magrys, Mainwaring, & Richards, 2010), and two summarized experimental mTBI treatments (Comper, Bisschop, Carnide, & Tricco, 2005;Snell, Surgenor, Hay-Smith, & Siegert, 2009). Table 2 summarizes quantitative study information (e.g., study quality, sample size) as well as reported overall effect size estimates for each meta-analysis and their associated U 1 /2 and U G /2 statistics.…”
Section: Resultsmentioning
confidence: 99%
“…Included in the online supplemental materials, Appendix A includes the references for all 131 studies. cognitive outcomes (Comper, Hutchison, Magrys, Mainwaring, & Richards, 2010), and two summarized experimental mTBI treatments (Comper, Bisschop, Carnide, & Tricco, 2005;Snell, Surgenor, Hay-Smith, & Siegert, 2009). Table 2 summarizes quantitative study information (e.g., study quality, sample size) as well as reported overall effect size estimates for each meta-analysis and their associated U 1 /2 and U G /2 statistics.…”
Section: Resultsmentioning
confidence: 99%
“…In such situations it can sometimes be very difficult to establish a diagnosis of mild TBI definitively. Definitions of mild TBI vary considerably across studies (Comper et al, 2005). The American Congress of Rehabilitation Medicine has presented criteria for mild TBI, defining a loss of consciousness (LOC) of less than 30 min, and posttraumatic amnesia (PTA) of less than 24 h (American Congress of Rehabilitation Medicine, 1993).…”
Section: Maas Et Almentioning
confidence: 99%
“…Three systematic reviews reported only one clinical trial of a pharmacological intervention for concussion. [23][24][25] One study showed no effect of nasal vasopressin on cognitive symptoms secondary to mild TBI. 26 A systematic review identified studies investigating interventions initiated in the ED for short-term (one week) and medium term (one month) outcomes in adults and children who sustained mild TBI.…”
Section: Discussionmentioning
confidence: 99%